The Influence of Online Social Support with Self-Disclosure on Instagram, Mediated by Confidence in Generation Z - Miftahussa’adah Miftahussa’adah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Generation Z, which is different from the previous generation, is closer to technology and information, in other words, generation Z tends to choose ways to solve their problems with technology, for example, when completing academic tasks they tend to look at ebooks and internet sources, where the internet now provides many new social networks through various applications and websites, one of which is the social media Instagram. The use of social media, of course, relates to the self-disclosure and online social support that is received and the confidence of its users. In this regard, this study aims to determine the relationship between online social support and self-disclosure mediated by self-confidence in generation Z. This study uses a quantitative research approach with purposive sampling data collection techniques. The subject of this study is generation Z.